2013
DOI: 10.1021/jz301956b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Density Functional Theory of Water

Abstract: Three dimensional implementations of liquid state theories offer an efficient alternative to computer simulations for the atomic-level description of aqueous solutions in complex environments. In this context, we present a (classical) molecular density functional theory (MDFT) of water that is derived from first principles and is based on two classical density fields, a scalar one, the particle density, and a vectorial one, the multipolar polarization density. Its implementation requires as input the partial c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
135
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 53 publications
0
135
1
Order By: Relevance
“…Molecular simulations could then provide reference data to validate DFT or even help build better functionals for that case [47]. Explicitly including the structure of the solvent [90][91][92] may also significantly improve the accuracy of the description of the confined fluid. In turn, classical DFT would also provide predictions at low salt concentrations, which are out of reach for molecular simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular simulations could then provide reference data to validate DFT or even help build better functionals for that case [47]. Explicitly including the structure of the solvent [90][91][92] may also significantly improve the accuracy of the description of the confined fluid. In turn, classical DFT would also provide predictions at low salt concentrations, which are out of reach for molecular simulations.…”
Section: Discussionmentioning
confidence: 99%
“…318 The functional was initially developed for the Molecular Density Functional Theory (MDFT), 163,164,[325][326][327] but can also be applied to 3D RISM. 318 The main idea behind this approach is to introduce a proper PMV correction for the correct initial state in the thermodynamic cycle of solvation to make the modelling results to be consistent with the isobaric-isotherm ensemble that is pertinent to experiments.…”
Section: Initial State Correction Sfe Functionalsmentioning
confidence: 99%
“…By benchmarking the MDFT results against MD simulations, Borgis and co-workers found that such approach is able to provide accurate results for different solute-solvent systems. 163,164,[325][326][327] The first attempt to perform massive SFE calculations (for ∌ 500 molecules) by MDFT combined with the PMV-based thermodynamic ensemble correction (see Section 5.5) demonstrates the high potential ) dissolved in polar solvents (water, PC and DMC). Note a break of the ordinate at 2 mol/kcal.…”
Section: Note On Alternative Distribution-function Approachesmentioning
confidence: 99%
“…65,66 The MDFT approach considers the excess free energy of a liquid in terms of the number and polarisation density up to the second order but required a three-body correction to reproduce the tetrahedral structure of water. 66 Our treatment of φ and ψ also begins by considering the polarisation density, but we capture many-body interactions by expanding correlation functions in the basis set of rotational invariants. We find correlations in polarisation density, described by φ, accounts for a majority of the ∆S and ∆C p of solvation.…”
Section: Comparison Of Parameter-free Modelsmentioning
confidence: 99%